1945
DOI: 10.1084/jem.81.5.469
|View full text |Cite
|
Sign up to set email alerts
|

The Regenerative Cycle of Motoneurons, With Special Reference to Phosphatase Activity

Abstract: 1. The regenerative cycle of motoneurons after axon amputation is described, and an attempt made to correlate morphological and chemical events in cell bodies with the growth requirements of regenerating axons. 2. The "normal" pattern of Nissl material in the cell is considered to be the resultant of a steady state in cytoplasmic nucleoprotein. Chromatol is then interpreted as a shift of the balance of nucleoprotein turnover in fa of degradation. The rapid early depletion of Nissl substance in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

1949
1949
1976
1976

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(25 citation statements)
references
References 42 publications
(53 reference statements)
2
22
1
Order By: Relevance
“…During a 2-week period the Nissl bodies break into smaller and smaller bits and diminish in quantity, the nucleus is displaced toward the periphery of the cell, and swelling of the cell body occurs. The climax of anatomical change comes in the 3rd week, and then alterations previously observed revert to normal over a period of 50-100 days (Bodian & Mellors, 1945). The changes in the function of the inferior mesenteric ganglion described above parallel this orderly sequence of anatomical events.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…During a 2-week period the Nissl bodies break into smaller and smaller bits and diminish in quantity, the nucleus is displaced toward the periphery of the cell, and swelling of the cell body occurs. The climax of anatomical change comes in the 3rd week, and then alterations previously observed revert to normal over a period of 50-100 days (Bodian & Mellors, 1945). The changes in the function of the inferior mesenteric ganglion described above parallel this orderly sequence of anatomical events.…”
Section: Discussionsupporting
confidence: 52%
“…The discovery of physiological effects of axotomy has led to renewed study of the axonal reaction in spinal motoneurones (Barr & Hamilton, 1948) and to the discovery of parallel changes in certain enzymic activities and other biological phenomena in them (Howe & Mellors, 1945;Bodian & Mellors, 1945). Chromatolysis is known to occur in autonomic ganglia on postganglionic axotomy (De Castro, 1932), but systematic studies of its temporal course or of the biochemical changes which may accompany it in this tissue do not appear to have been reported.…”
mentioning
confidence: 99%
“…This fibre shrinkage, amounting to some 10 %, can be compared with the axonal shrinkage which takes place in the central stump of a regenerating peripheral nerve (Gutmann & Sanders, 1943;Sanders & Whitteridge, 1946). If, as seems likely, fibre shrinkage of this kind takes place because outflow of axoplasm exceeds its rate of manufacture during regeneration, with consequent reduction of axonal turgor (Bodian & Mellors, 1945), then it appears impossible to achieve fully the aim of silencing presynaptic pathways by operation without altering such pathways in any other respect. Nevertheless, it is considered that this complication does not seriously weaken the significance of the data to be presented, though the arguments favouring this conclusion must be deferred until the experimental results have been fully described.…”
Section: Hitologymentioning
confidence: 99%
“…
When the axon of a neurone is severed, the cell body exhibits a profound series of morphological and chemical changes (the axon-reaction or chromatolysis) that begins a few days later and reaches a maximum in 2-3 weeks (Cajal, 1909;Bielschowsky, 1932; Hyden, 1943;Nonidez, 1944;Bodian & Mellors, 1945; Brattgard, Edstrom & Hyden, 1957).It has been shown that, concomitant with these morphological changes, chromatolysed motoneurones exhibit changes in their reflex responses (Downman, Eccles & McIntyre, 1953). At the height of the chromatolysis group I afferent volleys from muscles no longer evoked a monosynaptic reflex discharge having the characteristic features of brief latency and virtual synchrony.
…”
mentioning
confidence: 99%